2014
DOI: 10.1002/ange.201400491
|View full text |Cite
|
Sign up to set email alerts
|

Co‐existence of Two Different α‐Synuclein Oligomers with Different Core Structures Determined by Hydrogen/Deuterium Exchange Mass Spectrometry

Abstract: Neurodegenerative disorders are characterized by the formation of protein oligomers and amyloid fibrils, which in the case of Parkinson’s disease involves the protein α‐synuclein (αSN). Cytotoxicity is mainly associated with the oligomeric species, but we still know little about their assembly and structure. Hydrogen/deuterium exchange (HDX) monitored by mass spectrometry is used to analyze oligomers formed by wild‐type (wt) αSN and also three familial αSN mutants (A30P, E46K, and A53T). All four variants show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 55 publications
4
57
0
1
Order By: Relevance
“…This particular mutant is different from the others, as well as from WT a-Syn, based on its very long lifetimes for both types of dimer and its relatively high population of type 2 dimers, which was more than twofold higher than that of WT a-Syn type 2 dimers. It has been shown recently that two structurally different a-Syn oligomers coexist for all four dimer species, A30P, E46K, A53T, and WT (57). One type of oligomer was reported to result in fibrillization, whereas the other was responsible for oligomerization.…”
Section: Role Of Mutations In A-syn Dimerization and Aggregationmentioning
confidence: 99%
“…This particular mutant is different from the others, as well as from WT a-Syn, based on its very long lifetimes for both types of dimer and its relatively high population of type 2 dimers, which was more than twofold higher than that of WT a-Syn type 2 dimers. It has been shown recently that two structurally different a-Syn oligomers coexist for all four dimer species, A30P, E46K, A53T, and WT (57). One type of oligomer was reported to result in fibrillization, whereas the other was responsible for oligomerization.…”
Section: Role Of Mutations In A-syn Dimerization and Aggregationmentioning
confidence: 99%
“…Force spectroscopy [40] and other methods [39] showed that a-synuclein oligomer stability, b-sheet content, and size of the solvent-exposed hydrophobic surfaces increased with the oligomer size. Analytical ultracentrifugation (AUC) measurements combined with the H/D exchange [41,42] and fluorescence analyses [43] have shown that amyloid core (residues 40-80) is consistently protected from the solvent in oligomers, and in some oligomer preparations this protection is extended on all N-terminal half of the protein (residues 1-90) [41]. Oligomers with smaller solvent-protected core were shown to be not on the pathway to fibril formation, whereas the oligomers with larger protected core were easily converted to fibrils [41,44].…”
Section: A-synuclein Oligomersmentioning
confidence: 99%
“…Moreover, they are very stable and resist both extreme temperature and extreme pH, and only high urea concentrations induce dissociation into monomers [24]. It should also be noted that the oligomers are complex species and do not represent a single homogeneous state: hydrogen/deuterium exchange coupled with mass spectrometry has revealed the co-existence of structurally and dynamically different oligomers, which however share the same core sequence (Y39-T75) [16].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, several different types of oligomers can be formed, depending on environmental conditions or additives [1,[5][6][7][8][9][10][11][12][13][14], making it difficult to compare data from different research groups. In this chapter we will focus on a type of stable αSN oligomers which we have characterized in our laboratory [1,[15][16][17][18]]. An accompanying chapter by Subramaniam and coworkers deals with oligomers made in a related manner [10,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%